한국어 경동사 논의에 대한 검토 - ‘하다’를 중심으로 - 정대식 (언어학, 0(76), 2016)
This paper is a critical review of a discussion of Korean light verb. Light verbs, compared to heavy verbs, are known to be semantically empty or have a blurred meaning. It is also known that the light verbs do not syntactically have argument structures as well as thematic roles. However, this paper illustrates that the typical light verb “hada”, does not have such properties. It is quite not easy to answer when we are asked what kind of meaning a vocabulary has. In fact, there are many cases that similar vocabularies are circularly defined in a dictionary. Although it is not easy to define the meaning of a vocabulary, we can identify it by examining whether if it shows any distinctiveness compared to other vocabularies that are in paradigmatic relation. The light verb “hada” has semantic distinctiveness from other vocabularies which have the same distribution. Korean predicative nouns are different with English predicative nouns. Every English predicative noun is derived from a verb, as it is demonstrated by its noun suffixes. On the other hand, Korean predicative is itself a noun by origin. The argument structures of verb and noun are different, since a verb takes the nominative case or the accusative case as its argument, while a noun takes the genitive case. This paper critically studies previous research which argued that a predicative noun had an argument structure, and claims that the argument structure is, in effect, taken by a compound word. It is illustrated that “hada” used in the construction of “X-hada”, operates as the root of a compound word when it takes verbal conjugation and operates as the root of an affix and an adjective when it takes adjectival conjugation. Furthermore, we observe that “hada” of “X-lɨl hada” is quite similar with English light verb complex predicate. Therefore, we regard “hada” as a light verb and propose a new analysis associated with. KCI Citation Count: 1